1982
DOI: 10.2337/diacare.5.1.31
|View full text |Cite
|
Sign up to set email alerts
|

Myocardial Infarction Site and Mortality in Diabetes

Abstract: Survival after a first myocardial infarction (MI) was examined in 54 diabetic and 270 nondiabetic subjects according to anatomic site of MI. Complete survival status information was obtained during a 12-yr follow-up. Compared with nondiabetic subjects, diabetics had a higher proportion of anterior site of MI below the age of 60 in both sexes. A significantly higher mortality was experienced in both sexes by patients with anterior MIs compared with other infarction sites (47% vs. 13% respectively, over 12 yr of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
1

Year Published

1983
1983
2016
2016

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(10 citation statements)
references
References 5 publications
0
9
0
1
Order By: Relevance
“…The lack of effect of duration is well recognized (14,24,30,43). However, several previous reports have found that the excess case fatality is more marked in women (11,13,30,32,43,44), and the Framingham study described a more marked excess of cardiovascular mortality, but not incidence, in women than in men (1). We found no relation between premorbid blood glucose control and hospital outcome.…”
Section: Discussionmentioning
confidence: 93%
“…The lack of effect of duration is well recognized (14,24,30,43). However, several previous reports have found that the excess case fatality is more marked in women (11,13,30,32,43,44), and the Framingham study described a more marked excess of cardiovascular mortality, but not incidence, in women than in men (1). We found no relation between premorbid blood glucose control and hospital outcome.…”
Section: Discussionmentioning
confidence: 93%
“…Other data [32] from a study involving 54 subjects and 270 normoglycaemic controls, also showed that anterior infarcts were more common (43% vs 13%) and had a significant adverse impact, the 60 day mortality being 55% in diabetic vs 31% in nondiabetic subjects. Other complications which appear more common are anterior wall rupture which is 2·7 times more likely and cardiogenic shock.…”
Section: Infarction Sitementioning
confidence: 89%
“…While Barrett-Connor, utilizing data from the Rancho Bernardo study, has focussed attention on the IHD mortality protection experienced by nondiabetic women (7), a number of other studies have suggested that diabetic women have a greater case fatality following a myocardial infarction than either men with diabetes or when compared to either gender without diabetes (39)(40)(41)(42)(43). This, however, is not a universal finding (44)(45)(46). It appears that the greatest increased case fatality occurs in women in the short term (30-60 days) rather than over the long term (41).…”
Section: Why Does Diabetes Cause a Greater Impact Onmentioning
confidence: 90%